2016
DOI: 10.1111/tpj.13136
|View full text |Cite
|
Sign up to set email alerts
|

A TILLING approach to generate broad‐spectrum resistance to potyviruses in tomato is hampered by eIF4E gene redundancy

Abstract: SUMMARYGenetic resistance to pathogens is important for sustainable maintenance of crop yields. Recent biotechnologies offer alternative approaches to generate resistant plants by compensating for the lack of natural resistance. Tomato (Solanum lycopersicum) and related species offer a model in which natural and TILLINGinduced potyvirus resistance alleles may be compared. For resistance based on translation initiation factor eIF4E1, we confirm that the natural allele Sh-eIF4E1 PI24 -pot1, isolated from the wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 64 publications
5
97
0
Order By: Relevance
“…In addition, the mRNA expression level of another copy is positively correlated with resistance durability. Taken together these results show that va ‐mediated resistance durability can be explained by redundancy/competition effects between members of the eIF4E gene family, parallel to what was recently shown in tomato (Gauffier et al , ).…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, the mRNA expression level of another copy is positively correlated with resistance durability. Taken together these results show that va ‐mediated resistance durability can be explained by redundancy/competition effects between members of the eIF4E gene family, parallel to what was recently shown in tomato (Gauffier et al , ).…”
Section: Introductionsupporting
confidence: 84%
“…A compatible eIF4E isoform is required by potyviruses for their genome translation, replication, stabilization, and intercellular and systemic transport (Contreras‐Paredes et al , ; Robaglia and Caranta, ; Sanfaçon, ; Wang and Krishnaswamy, ). Some potyviruses can also use several eIF4E isoforms in a given host (Gauffier et al , ; Jenner et al , ; Mazier et al , ; Xu et al , ). This suggests that in the absence of a functional eIF4E‐1 in va ‐resistant genotypes, RB PVY variants may use another eIF4E isoform, similar to the situation when TuMV overcomes an eIFiso4E loss‐of‐function in Arabidopsis through VPg mutations allowing recruitment of eIF4E1 (Bastet et al , ; Gallois et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TILLING has been commonly employed in many organisms (McCallum et al, 2000; Meksem et al, 2008; Moens et al, 2008; Dierking and Bilyeu, 2009; Colasuonno et al, 2016; Gauffier et al, 2016; Nida et al, 2016). To perform TILLING, a mutagenized population is developed using a chemical mutagen such as ethyl methanesulfonate (EMS).…”
Section: Introductionmentioning
confidence: 99%
“…It had been shown that engineering mutations in the host plant eIF4E through the use of the Targeting-Induced Local Lesions in Genome (TILLING) strategy could provide resistance against potyviruses in a range of plants (Julio et al, 2015; Gauffier et al, 2016). The CRISPR-Cas9 sgRNA system has now been used to efficiently inactivate these genes and generate virus-resistant plants (Chandrasekaran et al, 2016; Pyott et al, 2016).…”
Section: Genome Editing Using the Crispr-cas9 System In Plant Virologymentioning
confidence: 99%